(untitled) (Economics and region, 2019)
The article examines the process of forming a strategy for the development of tourism at the level of a united territorial community. It has been determined that the process of forming a tourism development strategy envisages the implementation of a number of organizational measures. Therefore, there was a need to develop documentation to ensure the development of tourism potential and develop a strategy. This will help not only to coordinate the actions of all participants (stakeholders), but also to provide a financial component. The strategy will allow the community to receive information that they (the state of tourist and recreational resources), to determine the potential and opportunities for further development. Set goals, objectives and performers, while taking into account the characteristics of the territories and their socio-economic situation. For analytical support of strategic analysis, it is proposed to use SWOT analysis and PESTLE analysis. This will allow to form a strategic vision of the development of tourism of a certain territorial community and its key factors for further development.